Student satisfaction toward food service cafeteria among university student in UiTM Perlis / Nor Asikin Ramli - Ramli, Nor Asikin (Universiti Teknologi Mara Perlis, 2020)
This study discusses on the student satisfaction about the university food service cafeteria in UiTM Perlis. Based on the framework, there are four main independent variables which are food quality, price fairness, ambience and staff performance and one dependent variable which is student satisfaction used in this study. This research was conducted at UiTM Arau, Perlis which the students are the respondents for this research. A total 10 questionnaires were distributed as pilot study. The objective of this study is to identify about the satisfaction of the university student about the food service cafeteria.